Adenosine Monophosphate-Activated Protein Kinase, Oxidative Stress, and Diabetic Endothelial Dysfunction - Zou, Ming-Hui; Wu, Shengnan (Cardiology discovery, 2021)
Endothelial dysfunction characterized by impaired endothelium-dependent vaso-relaxation is one of the earliest detectable pathological events in smoking, diabetes, and many cardiovascular diseases including hypertension, atherosclerosis. Overwhelming data from human and animals demonstrate that the endothelial dysfunction associated with diabetes is due to the local formation of oxidants and free radicals. However, the mechanisms by which diabetes instigates oxidative stress, and those by which oxidative stress perpetuates endothelial dysfunction are the subjects of intensive research in the last 3 decades. The studies from us and others have demonstrated that adenosine monophosphate-activated protein kinase (AMPK), a well-characterized energy sensor and modulator, serves as a highly efficient sensor as AMPK can be activated by very low levels of reactive oxygen species (ROS) and reactive nitrogen species (RNS) generated by physiological, pharmacological, and pathologic stimuli (redox sensor). Interestingly, oxidants-activated AMPK feedback lowers the levels of ROS by either suppressing ROS/RNS from reduced nicotinamide adenine dinucleotide phosphate (NADPH) oxidase and mitochondria or by increasing the levels of antioxidant enzymes (redox modulator). Further, our studies demonstrate that AMPK's functions as a redox sensor and modulator are vital to maintain endothelial cell function under physiological conditions. Finally, we discover that under chronic oxidative stress or large influx of ROS, AMPK is particularly susceptible to inhibition by ROS. We conclude that oxidative inactivation of AMPK in diabetes perpetuates oxidative stress and accelerates atherosclerosis in diabetes.